2020
DOI: 10.1021/acssensors.0c00484
|View full text |Cite
|
Sign up to set email alerts
|

Protein Discrimination Using a Fluorescence-Based Sensor Array of Thiacarbocyanine-GUMBOS

Abstract: Sensitive and selective detection of proteins from complex samples has gained substantial interest within the scientific community. Early and precise detection of key proteins plays an important role in potential clinical diagnosis, treatment of different diseases, and proteomic research. In the study reported here, six different compounds belonging to a group of uniform materials based on organic salts (GUMBOS) have been synthesized using three thiacarbocyanine (TC) dyes and employed as fluorescent sensors. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 70 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…Abbasi-Moayed and co-workers have established a nanopaper-based ratiometric fluorescent sensor array using nanohybrids for the discrimination of heavy metal ions by RGB analysis . Pérez et al have reported a thiacarbocyanine dye-based sensor array for the discrimination of proteins at various concentrations . Although fluorescent sensor arrays have been widely used to detect and discriminate the heavy metal ions, phosphates, toxic gases, and other chemicals, , their application to identify active/toxic ingredients in herbal medicines has only been limited to a single species to date .…”
Section: Introductionmentioning
confidence: 99%
“…Abbasi-Moayed and co-workers have established a nanopaper-based ratiometric fluorescent sensor array using nanohybrids for the discrimination of heavy metal ions by RGB analysis . Pérez et al have reported a thiacarbocyanine dye-based sensor array for the discrimination of proteins at various concentrations . Although fluorescent sensor arrays have been widely used to detect and discriminate the heavy metal ions, phosphates, toxic gases, and other chemicals, , their application to identify active/toxic ingredients in herbal medicines has only been limited to a single species to date .…”
Section: Introductionmentioning
confidence: 99%
“…Biosensing of mixtures of biomarkers and/or proteins is of particular interest for disease diagnosis and treatment [181][182][183]. Many current methods, such as enzyme-linked immunosorbent assay (ELISA) or polyacrylamide gel electrophoresis (PAGE) coupled to mass spectrometry, require expensive resources and labor intensive steps [183][184][185]. Organic salts are of increasing interest for development of fluorescent sensor arrays for protein detection and discrimination as they are easily tunable for increasing hydrophobicity, traditionally more stable upon ion exchange, and require little resources for purification [90].…”
Section: Differential Sensing: Biological Applicationsmentioning
confidence: 99%
“…To acquire high FRET efficiency between ERD dye and acceptor photosensitizer, a new class of compound, ionic materials (IMs), is presented in this work. IMs are tunable ionic salts that share properties of ionic liquids but are solid at room temperature [21][22][23]. IMs are ideal for several applications due to their enhanced photo and thermal stability, fluorescence quantum yields, and electrochemical characteristics [10,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…IMs are tunable ionic salts that share properties of ionic liquids but are solid at room temperature [ 21 - 23 ]. IMs are ideal for several applications due to their enhanced photo and thermal stability, fluorescence quantum yields, and electrochemical characteristics [ 10 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%